VACUUM HEAT TREATMENT OF ENGINEERING MATERIALS; THE TECHNICAL ASPECT (Biological Sciences - PJSIR, 2001)
In view of the rapid technological development taking place around the globe, advanced materials processing comes intosharp focus. Heat treatment in vaccum offers a plausible alternative over conventional heat treatment process as theformer allows to heat treat finished parts and components with minimum surface degradation. The paper reviewsvarious vacuum heat treating processes and their advantages over the conventional processes with specific reference tonuclear, missile and aerospace materials.